1997
DOI: 10.1046/j.1365-3083.1997.d01-167.x
|View full text |Cite
|
Sign up to set email alerts
|

Studies in Knockout Mice Reveal that Anti‐Chlamydial Protection Requires TH1 Cells Producing IFN‐γ: Is this True for Humans?

Abstract: Chlamydia trachomatis is one of the major causes of infertility and preventable blindness in the world. The organism is of particular interest from an immunological point of view because it is one of the few obligate intracellular bacterial pathogens. There is some evidence that repeated infections in humans stimulate protective immunity. However, until recently, it was unclear which components of the adaptive immune system give rise to protection. Studies in gene knockout mice reported here and elsewhere now … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
76
1

Year Published

1999
1999
2014
2014

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(80 citation statements)
references
References 31 publications
(42 reference statements)
3
76
1
Order By: Relevance
“…We and others have previously shown that CD4 ϩ T cells are critical in the clearance of a genital tract infection with C. trachomatis (3,25,26). Very few CD4 ϩ T cells were found in the genital tract of naive mice (Fig.…”
Section: Cd3 ϩ B220 Low T Cells May Be Involved In Pregnancy But Appementioning
confidence: 92%
See 2 more Smart Citations
“…We and others have previously shown that CD4 ϩ T cells are critical in the clearance of a genital tract infection with C. trachomatis (3,25,26). Very few CD4 ϩ T cells were found in the genital tract of naive mice (Fig.…”
Section: Cd3 ϩ B220 Low T Cells May Be Involved In Pregnancy But Appementioning
confidence: 92%
“…D espite much interest in the mechanisms of immune protection against sexually transmitted diseases (STD), 3 few detailed studies have been performed of the phenotype, distribution, and function of lymphocytes found in the genital tract mucosa. In particular, a better knowledge about genital tract T cells is needed to understand not only host protection against STD, but also how tolerance is established in pregnancy to avoid rejection of the fetus.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Chlamydia muridarum, formally called C. trachomatis mouse pneumonitis (MoPn), 2 is commonly used in mouse models of respiratory and genital tract infections (10). It has been demonstrated that the pattern of cytokine responses is important in the regulation of immune responses to Chlamydia (11,12), and T cell-mediated immunity is the major protective mechanism against chlamydial infection (13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23). It was reported that trachoma patients with severe conjunctival scarring show impaired cell-mediated immune responses and low IFN-␥ production with high levels of IgG Ab production (24 -26).…”
mentioning
confidence: 99%
“…We previously found that the mouse strain that produces higher organism-driven IFN-␥ production shows significantly more resistance to chlamydial infection (10,17) and that IFN-␥ gene knockout (KO) mice, IL-12 KO mice, and IL-18 KO mice exhibit much more serious diseases when compared with wild-type mice (27,28). Studies by other groups also demonstrated the extreme importance of IFN-␥ and Th1 immune responses in host defense against chlamydial infection (14,22,23,25). Dendritic cells (DC) have been shown to be the most efficient APC in priming T cells.…”
mentioning
confidence: 99%